Un four de terre cuite architecturale de la fin du Moyen Âge ou de l’époque moderne à Gournay (Centre, Indre) - Stéphane Joly; Jérôme Bouillon (Revue Archéologique du Centre de la France)
A brief excavation at Gournay (Indre) in the center of France, led to the identification of a production unit of architectural terracotta, as also the kiln’s outline. They are supposed to date from the end of the Middle Ages or the beginning of early modern period. Some of the finds from nearby (pits and a pond) are probably part of this workshop. Similar findings are rare in this region and they are almost exclusively of ancient excavations. The kiln from Gournay is thereby a new data completing an heterogeneous corpus, often fragmentary and quite characteristic of the current state of research on the craft of architectural terracotta during the medieval and modern periods.